Possible Clues to the East Polynesian Homeland: Paper Mulberry, Sweet Potato and Red-flowered Hibiscus - Davletshin, Albert (Waka Kuaka, 2023)
Several words designating economically important plants and objects in East Polynesian languages show a peculiar sound change: the loss of a labial consonant (*p, *m or *f) in contact with both a rounded vowel (*o or *u) and an unrounded one (*i, *e or *a), in polymoraic words more than two morae long. Such words seem to originate from a hypothetical East Polynesian language whose speakers were responsible for introducing ‘paper mulberry’, ‘sweet potato’, ‘girdles plaited from banana leaves’, ‘bowls for pounding food’ and ‘cultivated red-flowered hibiscus’ to their neighbours. The language may have been spoken in the Southern Cook Islands, where the highest number of words with lost labial consonants is found. One of the words under discussion, ‘red-flowered hibiscus’, is also attested in the languages of West Polynesia, Fiji, Rotuma, Anuta, Tikopia and the Central Northern Polynesian Outliers. This distribution indicates that the Southern Cook Islands were a locus of interaction between speakers of West and East Polynesian languages before the settlement of Remote East Polynesia, that is to say, a place where East Polynesians maintained their ancestral connections. This implies that the Southern Cooks may have been the East Polynesian homeland.